Pengaruh Teknologi Informasi Dan Kualitas Layanan Terhadap Kepuasan Nasabah Bank BCA Cabang KCU Tanjung Priok - Naufaliani, Nabila; Widyawan, Bisma (JAMBIS : Jurnal Administrasi Bisnis, 2025)
In recent years, Bank BCA Tanjung Priok branch has experienced obstacles and problems in every service, resulting in customer complaints and a decrease in the number of customers who transact directly to the branch and an increase in the number of customers who transact digitally. This is related to information technology and service quality. This study aims to test and analyze the influence of information technology and service quality on customer satisfaction at Bank BCA Tanjung Priok branch. Respondents in this study were customers of Bank BCA Tanjung Priok branch. The research method used is a quantitative method. The sampling technique used a random sampling method with a sample size of 100 respondents. Based on the analysis conducted, this study shows that "Information Technology and Service Quality have an influence on Customer Satisfaction" and have a significant influence. The results of the study indicate that based on the results of the T-test, the independent variables in this study have a positive effect on the dependent variable. Based on the results of the F test that has been carried out, the calculated F obtained is greater than the F table so that there is a simultaneous influence on the variables of information technology and service quality on customer satisfaction at Bank BCA, Tanjung Priok branch. In the determination coefficient test (R2), the results obtained were 53.9% of the independent variables of information technology and service quality were able to explain variations in work productivity, while 46.1% was explained by other variables outside this study.